Interferon-induced transmembrane protein-3 genetic variant rs12252-C is associated with disease severity in COVID-19 - Zhang, Y; Qin, L; Zhao, Y; Zhang, P; Xu, B; Li, K; Liang, L; Zhang, C; Dai, Y; Feng, Y; Sun, J; Hu, Z; et al. (Oxford University Press, 2020)
A major unanswered question in the current global COVID-19 outbreak is why a small minority of infected individuals develop severe disease. Here we report that homozygosity for the C allele of rs12252 in the interferon-induced transmembrane protein 3 (IFITM3) gene is associated with more severe disease in an age dependent manner. This supports a role for IFITM3 in disease pathogenesis and the opportunity for early targeted intervention in at risk individuals.